Intranasal HD-Ad-FS vaccine induces systemic and airway mucosal immunities against SARS-CoV-2 and systemic immunity against SARS-CoV-2 variants in mice and hamsters - Zhou, Peter; Watt, Jacqueline; Mai, Juntao; Cao, Huibi; Li, Zhijie; Chen, Ziyan; Duan, Rongqi; Quan, Ying; Gingras, Anne-Claude; Rini, James M.; Hu, Jim; Liu, Jun (Frontiers in Immunology, 2024)
The outbreak of coronavirus disease 19 (COVID-19) has highlighted the demand for vaccines that are safe and effective in inducing systemic and airway mucosal immunity against the aerosol transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, we developed a novel helper-dependent adenoviral vector-based COVID-19 mucosal vaccine encoding a full-length SARS-CoV-2 spike protein (HD-Ad-FS). Through intranasal immunization (single-dose and prime-boost regimens), we demonstrated that the HD-Ad-FS was immunogenic and elicited potent systemic and airway mucosal protection in BALB/c mice, transgenic ACE2 (hACE2) mice, and hamsters. We detected high titers of neutralizing antibodies (NAbs) in sera and bronchoalveolar lavages (BALs) in the vaccinated animals. High levels of spike-specific secretory IgA (sIgA) and IgG were induced in the airway of the vaccinated animals. The single-dose HD-Ad-FS elicited a strong immune response and protected animals from SARS-CoV-2 infection. In addition, the prime-boost vaccination induced cross-reactive serum NAbs against variants of concern (VOCs; Beta, Delta, and Omicron). After challenge, VOC infectious viral particles were at undetectable or minimal levels in the lower airway. Our findings highlight the potential of airway delivery of HD-Ad-FS as a safe and effective vaccine platform for generating mucosal protection against SARS-CoV-2 and its VOCs.